The effect of linguistic background on rapid number naming: implications for native versus non-native English speakers on sideline-focused concussion assessments. (6th December 2018) - Rizzo, John-Ross; Hudson, Todd E.; Amorapanth, Prin X.; Dai, Weiwei; Birkemeier, Joel; Pasculli, Rosa; Conti, Kyle; Feinberg, Charles; Verstraete, Jan; Dempsey, Katie; Selesnick, Ivan; Balcer, Laura J.; et al.
ABSTRACT: Objective : To determine if native English speakers (NES) perform differently compared to non-native English speakers (NNES) on a sideline-focused rapid number naming task. A secondary aim was to characterize objective differences in eye movement behaviour between cohorts. Background : The King-Devick (KD) test is a rapid number-naming task in which numbers are read from left-to-right. This performance measure adds vision-based assessment to sideline concussion testing. Reading strategies differ by language. Concussion may also impact language and attention. Both factors may affect test performance. Methods : Twenty-seven healthy NNES and healthy NES performed a computerized KD test under high-resolution video-oculography. NNES also performed a Bilingual Dominance Scale (BDS) questionnaire to weight linguistic preferences (i.e., reliance on non-English language(s)). Results : Inter-saccadic intervals were significantly longer in NNES (346.3 ± 78.3 ms vs. 286.1 ± 49.7 ms, p = 0.001), as were KD test times (54.4 ± 15.1 s vs. 43.8 ± 8.6 s, p = 0.002). Higher BDS scores, reflecting higher native language dominance, were associated with longer inter-saccadic intervals in NNES. Conclusion : These findings have direct implications for the assessment of athlete performance on vision-based and other verbal sideline concussion tests; these results are particularly important given the international scope of sport. Pre-season baseline scores are essential to evaluation in the event of concussion, and performance of sideline tests in the athlete's native language should be considered to optimize both baseline and post-injury test accuracy.